Acute asthma in adults. Issue 4 (April 2013) - Rajakulasingam, Ramyah; Wilkinson, Alex; Wilkinson, Emily
Consultations related to asthma account for approximately 2–3% of GP encounters and 85% of asthma patients are managed solely in general practice. Uncontrolled asthma continues to be highly prevalent; in 2010 there were 1071 deaths from asthma in the UK. Exacerbations incur substantial costs to both the patient and the healthcare system. It is thus very important that all GPs and AiTs know how to manage acute asthma, are able to identify the 'at risk' patient and can arrange appropriate follow-up after acute exacerbations. This article aims to review current knowledge of acute asthma in adults, with an emphasis on management in a primary care setting according to the latest national guidelines.